Novel Natural Inhibitors Targeting Enhancer of Zeste Homolog 2: A Comprehensive Structural Biology Research - Li, Weihang; Ding, Ziyi; Zhao, Yunlong; Jiang, Min; Zhang, Shilei; Zhao, Hongzhe; Lei, Ke; Xu, Rui; Zhao, Yingjing; Wang, Dong; Chao, Min; Yin, Yanjiang; et al. (Frontiers in Oncology, 2021)
EZH2 （Enhancer of Zeste Homolog 2）is a methylated modification enzyme of Histone H3-Lys 27. The high expression of EZH2 in cells is closely related to the progression, invasion and metastasis of neoplasm. Therefore, this target is gradually becoming one of the research hotspots of tumor pathogenesis, and the inhibitors of the EZH2 enzyme are expected to become new anti-tumor drugs. This study used a series of virtual screening technologies to calculate the affinity between the compounds obtained from the ZINC15 database and the target protein EZH2, the stability of the ligand-receptor complex. This experiment also predicted the toxicity and ADME properties of the candidate drugs in order to obtain compounds with excellent pharmacological properties. Finally, the ligand-receptor complex under in-vivo situation was estimated by molecular dynamics simulation to observe whether the complex could exist steadily in body. The experimental results showed that the two natural compounds ZINC000004217536 and ZINC000003938642 could bind tightly to EZH2, and the ligand-receptor complex could exist stably in-vivo. Moreover, these two compounds were calculated to be non-toxic, they also had a high degree of intestinal absorption and high bioavailability. In-vitro experiments confirmed that drug ZINC000003938642 could inhibit the proliferation and migration of osteosarcoma, which could be served as potential lead compounds. Therefore, the discovery of these two natural products had broad prospects in the development of EZH2 inhibitors, providing new clues for the treatment or adjuvant treatment of tumors.